Digital Identity and Linguistic Innovation: A Corpus-Based Study of Nigerian English on Social Media - Edung, Augustine; Ekpang, Juliet; Tanyi, John; Arihi, Blessing (Universitas Negeri Makassar, 2025)
This study explores the linguistic features and pragmatic functions of Nigerian English (NE) as manifested on social media platforms, primarily Twitter and Instagram. It investigates how Nigerian users creatively manipulate the English language to construct a unique digital identity that reflects both global connectivity and local cultural nuances. The research adopts a corpus linguistics approach, compiling and analyzing a specialized digital corpus of posts, comments, and hashtags from Nigerian users. The analysis focuses on identifying and categorizing distinctive lexico-semantic innovations (e.g., semantic shifts, novel compounds), syntactic patterns, and pragmatic strategies such as code-mixing and humor. The study examines how these features operate within online communities to foster solidarity, express cultural concepts lacking in Standard English, and negotiate a distinctly Nigerian online presence. Findings will demonstrate that social media serves as a dynamic and fertile ground for the evolution and enregisterment of NE variants, moving beyond mere replication of standard forms to active and conscious linguistic creation. This research contributes to the fields of World Englishes and computer-mediated communication by documenting the organic, bottom-up development of a digital variety of NE and its role in contemporary identity formation.